Peak load reduction and resilience benefits through optimized dispatch, heating and cooling strategies in buildings with critical microgrids. (1st June 2023) - Rosales-Asensio, Enrique; Icaza, Daniel; González-Cobos, Noemi; Borge-Diez, David
Abstract: This research analyzes the combined peak reduction and resilience increase in critical buildings through the use of microgrids configured using a specific control system to provide correct power quality for local loads that can be either connected or disconnected from the grid, operating grid-connected or islanded mode. In case of grid failure, energy storage combined with one or several local generators can provide backup power and consider both conventional and renewable energy systems. This research focuses on the design of building energy systems that are able to maintain the energy supply and establishes a methodology to evaluate the resilience benefits of a microgrid integrated into critical buildings when power outages occur and the particular case of a hospital building is presented. The optimization of the dispatch and heating and cooling strategies are analyzed and a case study characterizing an electric polygeneration microgrid feeding critical loads is presented. Results show the benefits and the increased energy resilience achieved when using solar PV, electrochemical batteries, combined heat and power, TES water tanks, and absorption chillers and propose a design and optimization scheme that can be applied for similar buildings and extend to any facility with critical loads. Results show that these microgrids can be optimally designed to improve the resilience of critical energy systems and, simultaneously, achieve economic benefits. Results show that in the event of an outage the positive monetary effects last longer than the duration of the outage. Graphical abstract: Image 1 Highlights: Proposed methodology allows to maintain the energy supply in critical buildings. Resilience benefits of a microgrid integrated in critical facilities is evaluated. Optimization of the dispatch and heating and cooling strategies is presented. Results prove economic benefits using of an optimal resilient microgrid. An electric polygeneration microgrid feeding critical loads is presented.